Artikel Penelitian Perbandingan Air Perasan Daucus Carota L. Dengan Povidone Iodine Topikal Dalam Penyembuhan Luka Insisi Mencit - Yesi Nurmalasari; Nofita Nofita; Efrida Warganegara; Aprilia Indah Sijabat (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Injury is damage or loss of body tissue that occurs due to a factor that interferes with the body's protection system. These factors such as trauma, changes in temperature, chemicals, explosions, electric shock, or animal bites. Wound treatment as the first treatment to prevent infection, among others, using antiseptics such as povidone iodine. one of the agents that can heal wounds and is easily sought after by the public because of its availability such as carrot bulbs. Carrot bulbs (Daucus carota L.) are effective as an antiseptic, strengthen liver function, urinate, get rid of useless substances through the kidneys, laxatives, and protect the body from toxic chemicals. Research Objective: To compare the effects of carrot tuber juice with 10% povidone iodine topically in wound healing so that it can be used as an alternative medicine to accelerate wound healing. Research Methods: The type of research to be conducted in this study is an experimental laboratory with a post test only group design method. Sampling was calculated using the Federer formula. Analysis of bivariate data with Shapiro-Wilk. Research Results: From a total of 24 mice research samples. Statistical analysis using the Shapiro-Wilk test showed p = 0.001. Conclusion: There was a significant difference (p <0.05) between each treatment group.